Agronomic performance of open pollinated and hybrid maize varieties: Results from on-farm trials in northern Ghana - van Asselt, Joanna; DI Battista, Federica; Kolavalli, Shashidhara; Udry, Christopher R. (International Food Policy Research Institute, 2018)
Maize is an important staple crop in Ghana, but maize productivity is low. Other countries with similar agroecological conditions have increased maize productivity by increasing the use of maize hybrids. This paper presents the results of maize trials in northern Ghana, in which hybrids were tested to see if they performed significantly better than the varieties planted by farmers. This paper details the procedures of the maize trials and presents descriptive statistics of the trial results. The trials demonstrated that two foreign hybrids performed consistently better than Obaatanpa, the most widely used variety in the north. The foreign hybrids performed consistently well in all districts and appear to be well-suited for planting in northern Ghana.